Physical Activity Decreases the Risk of Sarcopenia and Sarcopenic Obesity in Older Adults with the Incidence of Clinical Factors: 24-Month Prospective Study - Ribeiro Santos, Vanessa [UNESP]; Dias Correa, Bianca [UNESP]; De Souza Pereira, Caroline Galan [UNESP]; Alberto Gobbo, Luís [UNESP] (Taylor & Francis, 2020)
Background/Study: The occurrence of sarcopenia and sarcopenic obesity (SO) may be associated with modifiable behavioral factors such as insufficient physical activity (PA) and sedentary behavior. Thus, the aim of this study was to analyze the association of total physical activity (PA) and its different domains, as well as sedentary behavior with sarcopenia and SO in older adults with the incidence of clinical factors. Methods: Body composition was measured by dual energy X-ray absorptiometry (DXA), handgrip strength by dynamometer, physical function by physical tests, and PA and sedentary behavior were self-reported. Results: Older adults with low gait speed (HR = 5.99, 95%CI = 2.07–17.24 and HR = 4.44, 95%CI = 1.37–14.41) and insufficiently active in the occupational domain presented a higher risk of sarcopenia, independent of others PA domains, total PA and sedentary behavior. Older adults with low muscle mass (HR = 3.71, 95%CI = 1.15–11.96), low gait speed (HR = 4.15, 95%CI = 1.38–12.50), and high body fat (HR = 3.82; 95%CI = 1.18–12.37) and insufficiently active in the locomotion domain presented a higher risk of SO, independent of sex and age. Conclusion: The risk of sarcopenia and SO is higher in older adults with the incidence of clinical factors who are insufficiently active in the occupational and locomotion domains, respectively.